Population genetics for 23 Y-STR loci in Tibetan in China and confirmation of DYS448 null allele. (May 2015) - Ye, Yi; Gao, Jingshang; Fan, Guangyao; Liao, Linchuan; Hou, Yiping
Highlights: This study provided the first 23 Y-STR haplotype data set for Tibetan population. PPY23 marker set provided potent discriminatory power for forensic purpose in Tibetan population. Part of null types at DYS448 observed with PPY23 kit should be with caution. Their true type but not null could be obtained by other kit or methods. Abstract: Tibetan is one of 56 ethnic groups in China, where a level of genetic sub-structure might be expected. Although a global analysis of Y-chromosomal haplotype diversity for 23 STR loci and Y-STR databases with PPY23 kit were created with collaborative effort, there was a lack of data for Tibetan population. In this study we evaluated 248 unrelated male individuals of Chinese Tibetan living in the Tibet Autonomous Region to explore the underlying genetic structure of Tibetan populations. These samples were typed for 23 short-tandem repeat (STR) loci (DYS19, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS385ab, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, GATAH4, DYS481, DYS533, DYS549, DYS570, DYS576, and DYS643) by using PPY23 kit. A total of 224 different haplotypes were found. Haplotype diversity was 0.9990. Both R st pairwise analyses and multidimensional scaling plot showed the genetic structure of Tibetan population was significantly different from some of Chinese ethnic groups and neighboring populations. There were few interesting null features at DYS448 observed by PPY23 that deserved some comment. It revealed that PPY23 marker set provided substantially stronger discriminatory power in Tibetan population.